1980
DOI: 10.1111/j.1532-5415.1980.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Therapy and Breast Cancer in Postmenopausal Women†

Abstract: During the 6-year period 1972-77, 123 postmenopausal women with breast cancer either had the disease diagnosed at Wilford Hall USAF Medical Center or were referred there for therapy. Their ages ranged from 33 to 90 (mean, 56.6 years). Of these women 64.2 percent had never taken hormones, 25.2 percent were estrogen users, 4.9 percent were estrogen-progestogen users, 4.9 percent had a history of hormone usage, and 1 patient was using estrogen vaginal cream. In a subgroup of 27 clinic patients (1975-77 period) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For instance, the report of Hoover et al (30) purported to show a slight increase; but when the same case load was reviewed by another epidemiologist (31), the outcome was a slight decrease. Gambrell et al (32) found that the incidence was far less in their hormone‐treated patients than in an untreated control group. In our studies, we found the normally expected incidence (Table 2).…”
Section: The Female Climactericmentioning
confidence: 95%
“…For instance, the report of Hoover et al (30) purported to show a slight increase; but when the same case load was reviewed by another epidemiologist (31), the outcome was a slight decrease. Gambrell et al (32) found that the incidence was far less in their hormone‐treated patients than in an untreated control group. In our studies, we found the normally expected incidence (Table 2).…”
Section: The Female Climactericmentioning
confidence: 95%
“…There were 242 cases of breast cancer treated at Wilford Hall USAF Medical Center from 1972 through 1977 (17,18). lnfiltrating ductal carcinoma of the left breast was found in 2 males, ages 49 and 63, and the remaining patients were female.…”
Section: Role Of Exogenous Estrogens In Breast Cancermentioning
confidence: 99%
“…It took 7 years of prospective study and 10 years of ever increasing progestogen use to confirm the protective effect of added progestogen to estrogen replacement therapy upon the breast, although our earlier reports indicated a trend in this direction. 13,25,28,46,47 Apparently, it takes long-term progestogen use to reduce the risk of breast cancer in postmenopausal women. The reduction in the risk of endometrial cancer from added progestogen was confirmed during the first few years of our study and also has been demonstrated in several other studies.…”
Section: Decreased Risk Of Breast Cancer From Postmenopausal Progestomentioning
confidence: 99%